2013
DOI: 10.1177/0148607113487926
|View full text |Cite
|
Sign up to set email alerts
|

From Parenteral to Enteral Nutrition

Abstract: Growth was compromised during the transitional phase, likely related to decreased protein intake. Optimizing protein provision while PN is weaned is an important strategy to prevent postnatal growth failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(24 citation statements)
references
References 37 publications
2
21
0
1
Order By: Relevance
“…3 We also previously reported that the slowest extrauterine growth was during the transition phase, which predicted growth failure at discharge and was related to inadequate energy and protein intakes during this phase. 4 To address this vulnerable period and promote continued growth, we established a nutrient-based transition protocol that resulted in significantly improved energy and protein intakes during the transition phase. The improvements in growth outcomes observed are consistent with previous studies that found better growth with increasing energy and protein intake throughout the NICU stay, 1518 although these improvements were not specifically associated with the critical period of extrauterine growth failure during the transition phase in these studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3 We also previously reported that the slowest extrauterine growth was during the transition phase, which predicted growth failure at discharge and was related to inadequate energy and protein intakes during this phase. 4 To address this vulnerable period and promote continued growth, we established a nutrient-based transition protocol that resulted in significantly improved energy and protein intakes during the transition phase. The improvements in growth outcomes observed are consistent with previous studies that found better growth with increasing energy and protein intake throughout the NICU stay, 1518 although these improvements were not specifically associated with the critical period of extrauterine growth failure during the transition phase in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Although current nutrition recommendations aim to achieve postnatal growth rates approximating the intrauterine growth of a normal fetus of the same postmenstrual age, 1 we recently observed growth failure rates in our unit of close to 50%, with other studies reporting growth failure rates of 30%–97% among preterm infants. 24 Poor nutrition is associated with adverse short-term outcomes, including sepsis, chronic lung disease, and prolonged need for mechanical ventilation, as well as impaired cognitive and neurological development in the long term. 59 Therefore, maintaining adequate nutrition and growth in this high-risk population is an important goal in the neonatal intensive care unit (NICU).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nutrition course of the preterm infant has more recently been described as three discrete nutrition phases, i.e., the parenteral nutrition (PN) phase when the infant in entirely dependent on PN for nutrition, the enteral nutrition (EN) phase when the infant is fully established on milk feeds, and the transition (TN) phase [ 1 , 2 , 3 ] when PN is being weaned with advancing enteral feeds. The TN phase is an extremely complex nutritional period characterized by multiple nutrient sources (PN and EN), and has been reported to last from 7 [ 1 ] to 10 days [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, maintaining a gestational age appropriate amino acid supply is important for growth of individual organs and tissues, particularly the brain, and this is important to do as IV nutrition is gradually reduced and enteral feedings advanced, as far too often, IV nutrition is minimized before full enteral feedings are achieved, leading to often extensive periods in which total nutrition, particularly of protein, is insufficient [ 45 46 ].…”
Section: (Parenteral) Feedingmentioning
confidence: 99%